Peningkatan Mutu Simpan Buah dengan Coating Film Komposit Tapioka-Kitosan - Nur Rokhati (Prosiding Seminar Nasional Teknik Kimia "Kejuangan", 2015)
In the tropics, damage of fruit after harvest is a major problem that must be solved. This damage is usually caused by metabolic activity in progress at the fruit. If the respiration process involving oxygen from the environment is not controlled then it will accelerate maturity and decay of the fruit. Besides that, horticulture very risky contaminated by fungi and microbes. The results of the analysis of Fourier Transform Infrared (FTIR) and Scanning Electron Microscopy (SEM) showed that the mixing of chitosan and starch solution can produce a homogeneous film due to the interaction between the hydroxyl groups of starch and the amine groups of chitosan. Application of coating films on strawberries for the shelf life of 10 days was found that the lowest weight loss occurs in pure films of the high molecular weight chitosan (± 200 kDa), whereas the composite films of chitosan and starch which produces the lowest weight loss is the medium molecular weight chitosan (± 100 kDa). The low molecular weight chitosan (± 50 kDa) have the best antimicrobial activity. The addition of tapioca can reduce the antimicrobial activity of chitosan films.